Effect of activation and exfoliation on the formation of carbon nanosheets derived from natural materials. (April 2020) - Nuilek, K; Simon, A; Kurovics, E; Ibrahim, J F M; Varanasi, D; Baumli, P
Abstract: Carbon is abundantly found in nature with a wide range of applications. It can be synthesized through physical and chemical processes. Chemical activation is considered as a very efficient method to obtain carbon with high surface area and narrow micropore distribution. Among all the chemical activating agents, alkaline hydroxides such as potassium hydroxide (KOH) or sodium hydroxide (NaOH) are reported to be of high interest in the production of carbon with higher performance. In our research, Nettle stem and peanut shell (natural materials) were used as raw materials for the preparation of carbon. Natural structures of nettle and peanut shell consists of cellulose, which is an important precursor in the preparation of highly ordered carbon nanosheets. Aqueous solutions of KOH and NaOH were used for activation and sulphuric acid (H2 SO4 ) was used for exfoliation. The process employed here has yielded a high percentage of carbon nanostructured particles.